Wellness Innovation Lab - Variantzas, Bobbie (2023)

Climate Anxiety Among English-Speaking Youth in Québec - Pettem, Alexandre; Rengel, Fernanda (2023)

Wellness Innovation Lab : Workshop Guidebook - Leading English Education and Resource Network (LEARN); Percolab Coop (2023)

Mental Health in the Anthropocene : Climate Anxiety among Québec’s English-speaking Youth - Rengel, Fernanda; Pettem, Alexandre (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20

ARC Mental Health Information Series : D-MER Dysphoric Milk Ejection Reflex - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Eating Disorders - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Perimenopausal Depression - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Perinatal Loss and Grief - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : PMDD- Premenstrual Dysphoric Disorder - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Postpartum Anxiety - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Postpartum Depression - Assistance and Referral Centre (ARC) (2023)

ARC Mental Health Information Series : Substance Use Disorder in Women - Assistance and Referral Centre (ARC) (2023)

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 12

Communauté du CHSSN NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 12

Community NetLink - Community Health and Social Services Network (CHSSN) (2023)
Number of pages: 10

L’initiative sur la jeunesse et la santé mentale : Rapport d'impcat 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Au cours de la deuxième année de l'initiative sur la jeunesse et la santé mentale (surnommée « YMHI »), le CHSSN a soutenu 27 organismes communautaires avec plus de 373 partenariats dans 12 régions du Québec, y compris trois organismes provinciaux, dans le but principal d'améliorer l'accès aux services et aux ressources en matière de santé mentale pour les jeunes d’expression anglaise du Québec âgés de 15 à 29 ans. Chaque organisation s'est efforcée d'identifier les lacunes dans les services de santé mentale pour les jeunes, d'impliquer ces derniers dans la conception des programmes, d'établir des partenariats avec les écoles locales, les services de santé publique et d'autres organisations communautaires, d'adapter, de traduire et de produire des ressources, et d'offrir des activités et des programmes pour les jeunes afin de contribuer à combler certaines lacunes. Grâce à une communauté de pratique et à un soutien individualisé, le CHSSN aide les organismes communautaires à renforcer leurs connaissances, à travailler en réseau et à résoudre les problèmes liés à la mise en oeuvre de leur programme.

Youth Mental Health Initiative : Impact Report 2022-2023 - Community Health and Social Services Network (CHSSN) (2023)
Within the Youth Mental Health Initiative’s (YMHI) second year, CHSSN supported 27 community organizations with over 373 partnerships across 12 regions of Quebec including three provincial organizations, with the central goal of improving the access of mental health services and resources to Quebec’s English-speaking youth between the ages of 15-29. Each organization has worked to identify gaps in youth mental health services; engage youth in program design; partner with local schools, public health services and other community organizations; adapt, translate, and produce resources; and offer activities and programs for young people to help fill some of the gaps. Through a community of practice and individualized support, CHSSN helped community organizations to build their knowledge, network with each other and problem solve on program implementation.

La santé mentale à l’ère des réformes en santé : l’importance de l’accès aux services et la langue - Dialogue McGill (2023)

Disparités en santé mentale et ses déterminants chez les jeunes du secondaire au Québec selon la langue d’enseignement - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Disparités en santé mentale et ses déterminants chez les jeunes du secondaire au Québec selon la langue d’enseignement - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Disparities in Mental Health and Its Determinants Among Quebec High School Students by Language of Instruction - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Disparities in Mental Health and Its Determinants Among Quebec High School Students by Language of Instruction - Quebec English-speaking Communities Research Network (QUESCREN) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)
Number of pages: 20